A novel approach to study the effects of the high-fat diet on markers of Alzheimer’s disease in a genetically stratified Drosophila population - Yarosh, Vladyslava (2023)
A high-fat diet is emerging as a particularly influential risk factor for Alzheimer’s disease due to the strong association with gut dysbiosis, inflammation, oxidative and metabolic stress, and cognitive deficits. We suggest that disturbed cholesterol biosynthesis and metabolism are one of the major factors through which the diet can exert its influence on the markers of neurodegeneration. The blood-brain barrier (BBB) is an important protective mechanism which helps maintain cholesterol homeostasis and diet-induced oxidative stress is associated with its damage. We investigated the effects of the high-fat diet on these processes by assessing the brain cholesterol pool, lipid peroxidation levels, and morphological neurodegeneration of Drosophila mutants with familial and sporadic genetic predisposition. We also adapted two additional protocols which will be useful in further investigation of the role of high-fat in Alzheimer’s pathology: 1) assessment of the BBB integrity and 2) testing of the short- and long-term memory deficits using a T-Maze manufactured using a 3D Printer. Our findings demonstrate that the high-fat diet disturbs cholesterol homeostasis in both mutant groups, but lipid peroxidation and neurodegeneration are characteristic of familial mutants that present with much earlier disease onset.